Perbedaan Konsentrasi Perekat Pada Briket Bioarang Tandan Kosong Sawit Dengan Tongkol Jagung Terhadap Waktu Didih Air - Anggiono, Anggiono; Mulsari, Suharman Asti (STIKES Wira Husada Yogyakarta, 2014)
Background: the potential of biomass as an energy source alternative replacement for kerosene and liquefied petroleum gas. Biocharcoal briquettes is a solid fuel made from waste biomass. Manufacture of biocharcoal briquettes require an adhesive as terminating the powdered charcoal, in addition to gluten can affect the amount of heat and moisture content of biocharcoal briquettes. The purpose of this research is to know the difference in concentration of the adhesive on the biocharcoal briquettes empty palm bunches with corncob boiling water over time. Research methods: experimentation with a Static Group Comparison design. Biocharcoal briquettes of the empty palm bunches and biocharcoal briquettes corncob given concentration adhesive 600 cc, 700 cc, 800 cc and 900 cc to boil water as much as 1000 ml and seen the difference between water boiling between the concentration of gluten. Data were analyzed by Anova and T-test (t-test). Results: biocharcoal briquette palm bunches showed no significant difference between the boiling water with the use of different concentrations of adhesive on the significance 0.136 > 0.05 , while corncob briquettes there is a real difference between the boiling water with the use of different concentrations of adhesive on the significance 0.000 < 0.05 . There is no real difference between the boiling time difference biocharcoal briquettes empty fruit bunches of oil and corncobs with significance 0.421 > 0.05 . Conclusion: there is no real difference between water boiling time of biocharcoal briquettes empty palm bunches on the concentrations of different adhesives, while the biocharcoal briquettes corncob is the water boiling time real difference by using different concentrations of adhesive. There is no real difference between water boiling time briquettes palm bunches with corncobs.